PENGARUH TAGLINE DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN DI SHOPEE (STUDI KASUS PADA MAHASISWA INSTITUT STIAMI KAMPUS A ANGKATAN 2017) - Citra Millenia Venzha; Anita Maulina (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to determine the Influence of Taglines and Brand Ambassadors on Purchase Decisions at Shopee (Case Study on Students of Campus A STIAMI Institute of 2017). The study is conducted with the quantitative method. The data collection is conducted through questionnaires and literature. The populations of this study are the students of the Campus A STIAMI Institute of 2017. The study uses the Random Sampling for the sampling technique with the population sampling method. There are 206 samples. The study is analyzed with the multiple linear regression analysis using the help of the version 25 of the IBM Statistic software. The results show that Taglines have a significant and positive influence on Purchase Decisions at Shopee by 57.3%. Brand Ambassadors have a significant and positive influence on Purchase Decisions at Shopee by 44.3%. Both the taglines (X1) and Brand Ambassadors (X2) have a significant and positive influence on Purchase Decision (Y) simultaneously by 0.470 or 47.0%, while the remaining 53.0% is influenced by other variables that are not included in this study